Observation of Giant Angular Goos-Hanchen Shifts Enhanced by Surface Plasmon Resonance in Subwavelength Grating - Nikolai I. Petrov; Yuri M. Sokolov; Vladimir V. Stoiakin; Viktor A. Danilov; Vladimir V. Popov; Boris A. Usievich (Photonics, 2023)
The effect of the Goos-Hanchen (GH) angular shift for a visible light beam under the excitation of surface plasmon resonance (SPR) in a metal subwavelength grating has been investigated. Extremely large angular GH shifts have been demonstrated for a subwavelength grating with an optimal depth. The high sensitivity of the beam shape transformation and the GH shift to a change in the angle of incidence near the SPR has been shown by rigorous electromagnetic simulation and demonstrated experimentally. The focusing of the reflected beam near the subwavelength grating surface has been demonstrated.